The function is F and it’s complement is F’. Suppose there is a function as follows
F = x' y z' + x' y' z
We can find the complement of the function using two rule stated by DeMorgan’s Law.
- Change the OR gates with AND gates or change the AND gates with OR gates.
- Change each literal of the function with it’s complement.
Now, we will apply the above two principle in F to obtain F’.
F'= (x' y z' + x' y 'z)' = (x + y' + z).(x + y + z')
Consider more examples,
F = x y' + x' y F' = (x y' + x' y) = (x' + y).(x + y) Source: Digital Logic and Computer Design by Morris Mano
F = (AB' + C)D' + E F' = ((AB' + C)D' + E)' = ((AB' + C)' + D)(E') = ((A' + B ) . C') + D).(E') = (A' + B + D)(C' + D).(E') Source: Digital Logic and Computer Design by Morris Mano
F = (x + y' + z)(x' + z')(x + y) F' = ((x + y' + z)(x' + z')(x + y))' = ((x + y' + z)' + (x' + z')' + (x + y)')' =((x' y z')+(x z) + (x' y')) = x' y z' + x z + x' y' Source: Digital Logic and Computer Design by Morris Mano